Is intraoperative endoscopy safe in a child with Kasai procedure? - Vinayak S Pujari; Mathews K Thomas; Yatish Bevinaguddaiah; Tejesh C Anandaswamy (Wolters Kluwer Medknow Publications, 2012)
We report a case of venous air embolism which occurred during intraoperative endoscopy in a five-year-old boy who had undergone Kasai procedure in his infancy. The child had a cardiac arrest during the procedure from which he could not be resuscitated. The awareness about this complication would allow rapid diagnosis, which is vital to provide specific treatment and prevent fatal outcome.